The potential of a project-based ethno-STEM biotechnology e-module to promote students’ critical and creative thinking skills - Subagja Agustinus; Anna Permanasari; Eni Nuraeni; Indarini Dwi Pursitasari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
ology education in secondary schools is predominantly theoretical, abstract, and lacks relevance to the local context, making it difficult for students to understand the concepts and resulting in weak critical and creative thinking skills. This study investigates the current state of biotechnology education in high schools, focusing on students' critical thinking and creativity, as well as the integration of local wisdom through the Ethno-STEM approach. The objectives of this preliminary study are: 1) to assess students’ critical and creative thinking skills in biotechnology, 2) to identify challenges faced by teachers and students, 3) to explore the integration of local wisdom, and 4) to provide recommendations for developing project-based e-modules. Survey and interview results show that 70% of teachers report students struggling to analyze biotechnology issues, 60% observe low creativity, and 80% note minimal integration of local wisdom. Additionally, 65% of students find it difficult to solve complex problems, and 70% feel the material lacks real-life relevance. These findings were obtained through a descriptive qualitative approach using surveys and interviews, and analyzed through thematic interpretation and descriptive statistics to provide a deeper understanding of the needs and development potential of the e-module. This emphasizes the need for a project-based approach that integrates local wisdom to improve critical and creative thinking skills. This study recommends developing project-based e-modules that integrate local wisdom to engage students and enhance their problem-solving skills, become a foundation for future research and the development of more contextual and creative learning methods.Abstrak. Pembelajaran bioteknologi di sekolah menengah dominan bersifat teoretis, abstrak, dan kurang berkaitan dengan konteks local, sehingga peserta didik kesulitan memahami konsep, serta lemahnya keterampilan berpikir kritis dan kreatif. Penelitian ini mengkaji kondisi pembelajaran bioteknologi di SMA, dengan fokus pada keterampilan berpikir kritis dan kreatif siswa, serta integrasi kearifan lokal melalui pendekatan Ethno-STEM. Tujuan dari penelitian pendahuluan ini adalah: 1) menilai keterampilan berpikir kritis dan kreatif siswa dalam pembelajaran bioteknologi, 2) mengidentifikasi tantangan yang dihadapi guru dan siswa, 3) mengeksplorasi potensi integrasi kearifan lokal, dan 4) memberikan rekomendasi pengembangan e-modul berbasis proyek. Hasil survei dan wawancara menunjukkan bahwa 70% guru melaporkan kesulitan siswa dalam menganalisis isu bioteknologi, 60% mengamati rendahnya kreativitas, dan 80% mencatat minimnya penerapan kearifan lokal. Selain itu, 65% siswa merasa kesulitan memecahkan masalah kompleks, dan 70% merasa materi tidak relevan dengan kehidupan sehari-hari mereka. Temuan ini diperoleh melalui pendekatan deskriptif kualitatif dengan menggunakan survei dan wawancara, serta dianalisis melalui interpretasi tematik dan statistik deskriptif untuk memberikan pemahaman yang lebih mendalam mengenai kebutuhan dan potensi pengembangan e-modul. Hal tersebut menegaskan perlunya pendekatan berbasis proyek yang mengintegrasikan kearifan lokal untuk meningkatkan keterampilan berpikir kritis dan kreatif. Penelitian ini merekomendasikan pengembangan e-modul berbasis proyek yang mengintegrasikan kearifan lokal untuk meningkatkan keterlibatan siswa dan keterampilan pemecahan masalah, menjadi dasar bagi penelitian selanjutnya dan pengembangan metode pembelajaran yang lebih kontekstual dan kreatif.